Comparison of neutrophil to lymphocyte ratio with other prognostic markers affecting 30 day mortality in acute pulmonary embolism - ERER, AYŞEN; YALÇINKAYA, ERDEM; KABADAYI, FEYYAZ; ARIKAN, HÜSEYİN; ÇİMŞİT, NURİ ÇAGATAY; KARAKURT, SAİT (TURKISH ASSOC TUBERCULOSIS & THORAX, 2019)
Introduction: Identifying the prognostic factors for patients with acute pulmonary embolism (APE) play a critical role in determining of the treatment strategy and to reduce mortality. The aim of this study is to evaluate the prognostic value of Neutrophil to Lymphocyte Ratio (NLR) and compare NLR with other prognostic factors in APE. Materials and Methods: We retrospectively examined 550 cases of acute pulmonary embolism diagnosed by spiral computed tomographic angiography. A receiver operating characteristics (ROC) curve was used to determine the sensitivity and specificity of parameters and the optimal cut-off value for predicting mortality. Significance of each prognostic factors selected by univariate analysis confirmed using Cox regression model. Results: Baseline NLR, Platelet to Lymphocyte Ratio (PLR), N-terminal pro-Brain Natriuretic Peptide (NT-proBNP), and D-dimer values respectively were found significantly high in patients who died within 30 days (p < 0.05). Patients with high-risk status and sPESI > 2 points had a significantly higher short-term mortality rate (p < 0.05). Short-time mortality was found significantly higher in patients with NLR > 7.3 (p < 0.05). Cox regression analysis indicated that patient risk status and sPESI score were independent prognostic factors (p < 0.05). However, NLR was not found as a predictor of mortality in APE (p > 0.05). After the subgroup analysis of the study, in patients without comorbid diseases NLR, patient's risk status, sPESI score were found the predictor of mortality in APE (p < 0.05). Conclusion: The frequency of incidental nodule was found higher than in our country than in developed countries.
Keywords: Pulmonary embolism; neutrophil; lymphocyte; mortality; prognosis; MEAN PLATELET VOLUME; SEVERITY INDEX; VENOUS THROMBOEMBOLISM; COMPUTED-TOMOGRAPHY; RISK STRATIFICATION; EUROPEAN-SOCIETY; EARLY DEATH; D-DIMER; DYSFUNCTION; PREDICTORS